SISTEM INFORMASI MANAJEMEN PENGKLASIFIKASIAN HADIST SHAHIH BUKHARI DAN MUSLIM MENGGUNAKAN ALGORITMA NEURAL NETWORK - Rasenda, Rasenda; Rini, Nova; Supriatiningsih, Supriatiningsih (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
In the book of Bukhari and Muslim hadith there are 7008 hadith sentences, of the 7008 sentences the Hadith is not yet known a hadith included in the category of prohibitions or orders. By doing the classification, it will be easier for readers to understand the hadith. The classification of hadiths is done in several stages, including: pre-processing text, the use of word vector features, and modeling of neural network architecture with multilayer perceptron. The use of layers in neural networks and feature extraction with word vectors has proven to provide good results for the classification of hadiths. The results showed a fairly high degree of accuracy that is equal to 97.72% by using two layers and 256 neurons, this research can be used to classify hadiths which have the impact of making it easier for people to understand hadiths very well.